Development economics - Roland, Gerard (Upper Saddle River, New Jersey : Pearson Education Incorporation, 2014)
This undergraduate textbook is the first that comprehensively takes stock of the exciting new research that has taken place in recent years to gain an understanding of the role of institutions in economic development.
Chapter 1: The development gap -- Chapter 2: Poverty and inequality -- Chapter 3: Population growth -- Chapter 4: Economic growth -- Chapter 5: Structural change and development strategies -- Chapter 6: International trade and exchange rate -- Chapter 7: Institutions and economic development -- Chapter 8: Market and hierarchies -- Chapter 9: Political institutions -- Chapter 10: Legal and fiscal institutions -- Chapter 11: Culture -- Chapter 12: Rural land rights and contracts -- Chapter 13: Property rights and efficiency in urban areas -- Chapter 14: Market development -- Chapter 15: The role of credit markets in development -- Chaptter 16: Health care delivery in developing countries -- Chapter 17: Delivering education in developing countries -- Chapter 18: Delivery infrastructure in developing countries -- Chapter 19: Corruption -- Chapter 20: Conflict -- Appendix: Econometric Appendix
Includes bibliographical references and index.
Keywords: ECONOMIC DEVELOPMENT